Reproducible Derivation and Expansion of Corneal Mesenchymal Stromal Cells for Therapeutic Applications - Jabbehdari, Sayena (Transl Vis Sci Technol, 2020)
PURPOSE: A reproducible protocol for the production of corneal mesenchymal stem/stromal cells (cMSCs) is necessary for potential clinical applications. We aimed to describe successful generation and expansion of cMSCs using an explant method. METHODS: Corneoscleral rims of human cadaveric eyes were divided into four pieces and used as explants to allow outgrowth of cMSCs (passage 0, or P0). The cells were subcultured at a 1:10 ratio until passage 5 (P5). The characteristics as well as therapeutic effects of expanded cMSCs were evaluated both in vitro, using a scratch assay, and in vivo using epithelial debridement and chemical injury mouse models. RESULTS: All explants demonstrated outgrowth of cells by 7 days. Although the initial outgrowth included mixed mesenchymal and epithelial cells, by P1 only cMSCs remained. By subculturing each flask at a ratio of 1:10, the potential yield from each cornea was approximately 12 to 16 × 10(10) P5 cells. P5 cMSCs demonstrated the cell surface markers of MSCs. The secretome of P5 cMSCs induced faster closure of wounds in an in vitro scratch assay. Subconjunctival injection of P5 cMSCs in mouse models of mechanical corneal epithelial debridement or ethanol injury led to significantly faster wound healing and decreased inflammation, relative to control. CONCLUSIONS: cMSCs can be reproducibly derived from human cadaveric corneas using an explant method and expanded with preservation of characteristics and corneal wound healing effects. TRANSLATIONAL RELEVANCE: The results of our study showed that cMSCs produced using this scheme can be potentially used for clinical applications.